PENGARUH PEMBERIAN PAKAN DENGAN EKSTRAK WORTEL (Daucus carota L) DAN EKSTRAK SPIRULINA TERHADAP WARNA IKAN KOI (Cyprinus carpio) - Prariska, Donny; Fahmi, Rizkan; Sumsanto, Muhammad (MAHSEER: Jurnal Ilmu-Ilmu Perairan dan Perikanan, 2023)
Ornamental fish are currently in great demand for cultivation. High selling value and productivity are the hallmarks of ornamental fish farming. One of the ornamental fish commodities that rely on the beauty of colors and patterns is koi fish. Koi fish that have a beautiful body shape and brilliant colors will increase the sale value. Increasing the color of fish plays an important role in koi fish farming. The colors that stand out in koi fish are red and orange. One way to increase the color is to provide feed containing carotenoids. Economical food ingredients containing carotenoids that can be added to feed include carrot and spirulina extracts. This study aims to determine which additional feed ingredients can have a better effect on the brightness of the color of koi fish. The parameters to be observed include color brightness and economic aspects. This study used a completely randomized design (CRD) with three treatments and three replications.